Serratus anterior plane versus paravertebral nerve blocks for postoperative analgesia after non-mastectomy breast surgery: a randomized controlled non-inferiority trial - Gabriel, Rodney A; Swisher, Matthew W; Sztain, Jacklynn F; Curran, Brian P; Said, Engy T; Abramson, Wendy B; Khatibi, Bahareh; Alexander, Brenton S; Finneran, John J; Wallace, Anne M; Armani, Ava; Blair, Sarah; et al. (Regional anesthesia and pain medicine, 2021)
BackgroundParavertebral and serratus plane blocks are both used to treat pain following breast surgery. However, it remains unknown if the newer serratus block provides comparable analgesia to the decades-old paravertebral technique.MethodsSubjects undergoing unilateral or bilateral non-mastectomy breast surgery were randomized to a single-injection serratus or paravertebral block in a subject-masked fashion (ropivacaine 0.5%; 20 mL unilateral; 16 mL/side bilateral). We hypothesized that (1) analgesia would be non-inferior in the recovery room with serratus blocks (measurement: Numeric Rating Scale), and (2) opioid consumption would be non-inferior with serratus blocks in the operating and recovery rooms. In order to claim that serratus blocks are non-inferior to paravertebral blocks, both hypotheses must be at least non-inferior.ResultsWithin the recovery room, pain scores for participants with serratus blocks (n=49) had a median (IQR) of 4.0 (0–5.5) vs 0 (0–3.0) for those with paravertebral blocks (n=51): 0.95% CI −3.00 to −0.00; p=0.001. However, the difference in morphine equivalents did not reach statistical significance for superiority with the serratus group consuming 14 mg (10–19) vs 10 mg (10–16) for the paravertebral group: 95% CI −4.50 to 0.00, p=0.123. Since the 95% CI lower limit of −4.5 was less than our prespecified margin of −2.0, we failed to conclude non-inferiority of the serratus block with regard to opioid consumption.ConclusionsSerratus blocks provided inferior analgesia compared with paravertebral blocks. Without a dramatic improvement in safety profile for serratus blocks, it appears that paravertebral blocks are superior to serratus blocks for postoperative analgesia after non-mastectomy breast surgery.Trial registration number NCT03860974.